2016
DOI: 10.4209/aaqr.2015.10.0579
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Measurement of Ambient Aerosol Liquid Water Content in Beijing

Abstract: The amount of liquid water present on ambient aerosol particles influences its radiative properties, the partitioning of gas-phase organic and inorganic compounds to the condensed phase, and the assessment of particle health effects upon inhalation. An improved home-made Dry-Ambient Aerosol Size Spectrometer (DAASS) was implemented and deployed at a sampling site in Beijing to measure water content and volumetric growth factor of fine ambient aerosol during clean and polluted days. Aerosol chemical composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
2
11
0
1
Order By: Relevance
“…In addition, higher uncertainties in NR-PM 1 measurements of low NR-PM 1 loadings and in ALW modelling at low RH may also contribute to the large variability. High ALW org /ALW in low aerosol mass concentrations is consistent with previous studies (Dick et al, 2000;Fajardo et al, 2016). Those studies showed that modelled ALW inorg was much lower than measured total ALW under low aerosol mass loadings in Beijing (Fajardo et al, 2016) and that ALW org was comparable to ALW inorg in low RH (Dick et al, 2000).…”
Section: Aerosol Liquid Water Contributed By Organicssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, higher uncertainties in NR-PM 1 measurements of low NR-PM 1 loadings and in ALW modelling at low RH may also contribute to the large variability. High ALW org /ALW in low aerosol mass concentrations is consistent with previous studies (Dick et al, 2000;Fajardo et al, 2016). Those studies showed that modelled ALW inorg was much lower than measured total ALW under low aerosol mass loadings in Beijing (Fajardo et al, 2016) and that ALW org was comparable to ALW inorg in low RH (Dick et al, 2000).…”
Section: Aerosol Liquid Water Contributed By Organicssupporting
confidence: 90%
“…Long-term data are needed to evaluate the amount of ALW and its interactions with aerosol organic compositions. So far, short-term ALW data in Beijing (Bian et al, 2014;Fajardo et al, 2016) have been collected by directly measuring size-resolved aerosol hygroscopic volume growth factors (VGFs) and particle size distributions using a hygroscopicity tandem differential mobility analyser (H-TDMA) (Rader and McMurry, 1986) or dry-ambient aerosol size spectrometer (DAASS) (Engelhart et al, 2011;Stanier et al, 2004). However, long-term measurements of ALW are rare because of the challenge in maintaining these instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, higher uncertainties in NR-PM1 measurements of low NR-PM1 loadings and in ALW modelling at low RH may also contribute to the large variability. High ALWorg/ALW in low aerosol mass concentrations is consistent with previous studies (Dick et al, 2000;Fajardo et al, 2016). Those studies showed that modelled ALWinorg was much lower than measured total ALW under low aerosol mass loadings in Beijing (Fajardo et al, 2016) and that ALWorg was 6 https://doi.org/10.5194/acp-2019-316 Preprint.…”
Section: Aerosol Liquid Water Contributed By Organicssupporting
confidence: 88%
“…Uptake of water by atmospheric particles modifies the mass of the aerosol particle and increases the particle size [30,31]. Previous studies have shown that particle diameter increases with increasing RH [32].…”
Section: Influence Of Rh On Secondary Particle Formationmentioning
confidence: 99%